Copyright Reduction as a Fidusia Warranty Object in Business Principles in Denpasar City - Dewa Gede Pradnya Yustiawan; I Wayan Werasmana Sancaya (Fakultas Hukum, Universitas Warmadewa, 2018)
Intellectual Property Rights as part of the legal system are closely related to the business world, especially with industry, trade and investment. With Intellectual Property Rights stimulated the improvement of intellectual works as well as research and development that are able to produce new techniques and technologies, which will excite the business world. Copyright is one part of intellectual property has the largest scope of protected objects, because it includes science, art and literature (art and literary) in which also includes computer programs. Copyright becomes the most important base of the national creative economy and has a strategic role in supporting the nation's development and promoting the general welfare as mandated by the 1945 Constitution of the State of the Republic of Indonesia. In Article 16 paragraph (3) Law Number 28 Year 2014 on Copyright determines that Copyright can be used as an object of fiduciary guarantee. In paragraph (4) it is determined that Copyright as the object of fiduciary guarantee as referred to in paragraph (3) shall be conducted in accordance with the provisions of applicable laws and regulations. From the provisions of Article 16 paragraph (3) and paragraph (4) above, Copyright as intangible moving object may be used as loan collateral (bank) by the creator or copyright owner with fiduciary burden and the imposition of the charge shall be based on legislation in banking field. Research on the imposition of Copyright as the object of fiduciary guarantee in banking practice in Denpasar City is done to know its implementation in banking practice. In addition, also to know the constraints faced by the bank if the credit agreement used Copyright as the object of fiduciary guarantee. By knowing that, the specific targets to be achieved in this research are the results can be used by the legislator to design and formulate the legal substance of the new drafting model of legal norms that regulate the guarantee, especially the Copyright as the object of fiduciary guarantee, so that more can guarantee the existence of legal certainty and business certainty for both creditor (bank) and debtor. This research is an empirical legal research and factual approach is done by looking at the real situation in the research area.